Screening plant materials for resistance to the yam nematode (Scutellonema bradys) - Oluwatayo, J.I; Asiedu, Robert; Adesiyan, S.O. (2010)
Experiments were carried out in the greenhouse and field of the Department of Crop Protection andEnvironmental Biology, University of Ibadan and the International Institute of Tropical Agriculture (IITA)to screen crops for resistance/susceptibility to the yam nematode Scutellonema bradys. The severity ofsusceptibility was closely associated with the number of nematodes that were recovered from the soil androots of plants. Field and greenhouse evaluation of the reactions of 10 yam cultivars TDr 87/0072, TRr 93– 31, TDr 131 (Dioscorea rotundata), TDa 92-2, TDa 85/00257, DAN 087 (D. alata), TDe 3041, TDe3037,TDe2786 (D. esculenta), Igangan (D. cayenensis) and seven other crops (Xanthosoma sagittifolium, Ipomoeabatatas, Zea mays, Cajanus cajan, Vigna subterranea, zingiber officicinale and Mucuna pruriens) to S.bradys showed significant (P<0.05) variation in dry rot incidence. TDa 92-2, Zea mays, Zingiber officinale,Xanthosoma sagittifolium and ipomoea batatas proved to be non-host to S. bradys as the nematodes wereunable to survive in the roots and cause damage. Variation in yield parameters (fresh weight of tubers,number of tubers per stand per plot and percentage dry matter) was significant at P<0.05. Results indicateallelopathy by the non-host crops. The gradual decline of nematode populations in plots planted with theresistant (non-host) plants confirms the ability of the plants to exude toxins and thereby survive the nematodeattack.